Competition of e-commerce intermediaries - Alexander Matros; Andriy Zapechelnyuk (Queen Mary University of London, School of Economics and Finance, 2010)
In e-commerce, where information collection is essentially costless and geographic location of traders matters very little, fierce competition between providers of similar services is expected. We consider a model where two e-commerce intermediaries (internet shops) compete for sellers. We show that two non-identical shops may coexist in equilibrium if the population of sellers is sufficiently differentiated in their time preferences. In such an equilibrium less patient sellers choose the more popular (with a higher rate of arrival of new buyers) and more expensive shop, while more patient sellers prefer the less popular and cheaper one.
Keywords: C73; D43; D82; 330; e-commerce; intermediary; competition; listing fee; closing fee; E-Business; Informationsbeschaffung; Internet; Wettbewerb